Multifunctional serine protease inhibitor-coated water-soluble gold nanoparticles as a novel targeted approach for the treatment of inflammatory skin diseases - Limón, David; Fábrega, María José; Calpena, Ana C.; Badia, Josefa; Baldomà, Laura; Pérez-García, Lluïsa (American Chemical Society, 2018)
The overexpression and increased activity of the serine protease Kallikrein 5 (KLK5) is characteristic of inflammatory skin diseases such as Rosacea. The use of inhibitors of this enzyme—such as 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride (AEBSF·HCl) or the anti-human recombinant Kallikrein 5 (anti-KLK5) antibody—in the treatment of the disease has been limited due to their low bioavailability, for which their immobilization in drug delivery agents can contribute to making serine protease inhibitors clinically useful. In this work, we synthesized gold nanoparticles (GNP) coated with a mixture of hydroxyl- and carboxyl-terminated thiolates (GNP.OH/COOH), whose carboxyl groups were used to further functionalize the nanoparticles with the serine protease inhibitor AEBSF·HCl either electrostatically or covalently (GNP.COOH AEBSF and GNP.AEBSF, respectively), or with the anti-KLK5 antibody (GNP.antiKLK5). The synthesized and functionalized GNP were highly water-soluble, and they were extensively characterized using UV–vis absorption spectroscopy, Transmission Electron Microscopy (TEM), Dynamic Light Scattering (DLS), and Thermogravimetric Analysis (TGA). GNP.OH/COOH and their subsequent functionalizations effectively inhibited KLK5 in vitro. Internalization of fluorophore-coated GNP.OH/COOH in human keratinocytes (HaCaT cells) was proven using confocal fluorescence microscopy. Cell viability assays revealed that the cytotoxicity of free AEBSF is importantly decreased when it is incorporated in the nanoparticles, either ionically (GNP.COOH AEBSF) or, most importantly, covalently (GNP.AEBSF). The functionalized nanoparticles GNP.AEBSF and GNP.antiKLK5 inhibited intracellular KLK5 activity in HaCaT cells and diminished secretion of IL-8 under inflammatory conditions triggered by TLR-2 ligands. This study points to the great potential of these GNP as a new intracellular delivery strategy for both small drugs and antibodies in the treatment of skin diseases such as Rosacea.